Blockchain: Is it the future for the tourism and hospitality industry?. Issue 2 (March 2022) - Önder, Irem; Gunter, Ulrich
Recently, blockchain and cryptocurrencies have become topics of discussion in both research and industry. Iansiti and Lakhani perceive blockchain as a foundational technology rather than a disruptive one, since potentially new economic and social systems can be based on blockchain. Therefore, understanding blockchain and contemplating its impact on the tourism and hospitality industry is essential. The tourism and hospitality industry has to focus not on the technology itself but on how it can be used for the benefit of consumers and suppliers, while at the same time creating new tourism products or systems. The purpose of this study is to explore and identify use cases for blockchain for the tourism and hospitality industry. In addition, an outlook on potential future blockchain applications given the current COVID-19 pandemic is provided.